The effect of ketogenic diet on behaviors and synaptic functions of naive mice. Issue 4 (7th March 2019) - Huang, Jie; Li, Yuan‐Quan; Wu, Cui‐Hong; Zhang, Yun‐Long; Zhao, Shen‐Ting; Chen, Yong‐Jun; Deng, Yu‐Hong; Xuan, Aiguo; Sun, Xiang‐Dong
Abstract: Introduction: Beyond its application as an epilepsy therapy, the ketogenic diet (KD) has been considered a potential treatment for a variety of other neurological and metabolic disorders. However, whether KD promotes functional restoration by reducing the pathological processes underlying individual diseases or through some independent mechanisms is not clear. Methods: In this study, we evaluated the effect of KD on a series of behaviors and synaptic functions of young adult naive mice. Wild‐type C57BL/6J mice at age of 2–3 months were fed with control diet or KD for three months. Body weight and caloric intake were monitored throughout the experiments. We assessed behavioral performance with seizure induction, motor coordination and activity, anxiety level, spatial learning and memory, sociability, and depression. Synaptic transmission and long‐term potentiation were also recorded. Results: KD‐fed mice performed equivalent to control‐diet‐fed mice in the behavioral tests and electrophysiological assays except exhibiting slower weight gain and increased seizure threshold. Conclusions: Our results contribute to the better understanding of effects of the KD on physiological behaviors and synaptic functions. Abstract : This is the first study to specially investigate the influence of long‐term feeding of the ketogenic diet (KD) on various behaviors and synaptic functions in young adult naive mice. We found that KD‐fed mice performed similarly to control‐diet‐fed mice on the behavioral tests and electrophysiological assays except exhibiting slower weight gain and increased seizure threshold.